Internal Migration, Remittances and Economic Development - Xiameng Pan; Chang Sun (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a quantitative spatial equilibrium model with endogenous migration and remittance decisions within households to examine the joint effect of migration and remittances on economic development. We apply the model to internal migration in China. Counterfactual analysis of the calibrated model shows that the presence of remittances increases migration and welfare, reduces regional inequality and facilitates structural change. Compared to a conventional single-person migration model, our household model suggests a larger reduction in regional inequality and stronger reallocation of employment from agriculture to manufacturing and services in response to the decline in migration costs over the period of 2000 to 2010.
Keywords: O10; R10; R20; 330; remittances; migration; structural change; spatial equilibrium